Boron-peptide conjugates with angiopep-2 for boron neutron capture therapy - Xiang, Jing; Ma, Lin; Tong, Jianfei; Zuo, Nan; Hu, Weitao; Luo, Yupeng; Liu, Junqi; Liang, Tianjiao; Ren, Qiushi; Liu, Qi (Frontiers in Medicine, 2023)
Boron neutron capture therapy (BNCT) induces intracellular nuclear reaction to destroy cancer cells during thermal neutron irradiation. To selectively eliminate cancer cells but avoid harmful effects on normal tissues, novel boron-peptide conjugates with angiopep-2, namely ANG-B, were constructed and evaluated in preclinical settings. Boron-peptide conjugates were synthesized using solid-phase peptide synthesis, and the molecular mass was validated by mass spectrometry afterwards. Boron concentrations in 6 cancer cell lines and an intracranial glioma mouse model after treatments were analyzed by inductively coupled plasma atomic emission spectroscopy (ICP-AES). Phenylalanine (BPA) was tested in parallel for comparison. In vitro treatment with boron delivery peptides significantly increased boron uptake in cancer cells. BNCT with 5 mM ANG-B caused 86.5% ± 5.3% of clonogenic cell death, while BPA at the same concentration caused 73.3% ± 6.0% clonogenic cell death. The in vivo effect of ANG-B in an intracranial glioma mouse model was evaluated by PET/CT imaging at 31 days after BNCT. The mouse glioma tumours in the ANG-B-treated group were shrunk by 62.9% on average, while the BPA-treated tumours shrank by only 23.0%. Therefore, ANG-B is an efficient boron delivery agent, which has low cytotoxicity and high tumour-to-blood ratio. Based on these experimental results, we expected that ANG-B may leverage BNCT performance in clinical applications in future.